The relationship between inequitable gender norms and provider attitudes and quality of care in maternal health services in Rwanda: a mixed methods study - Kate Doyle; Shamsi Kazimbaya; Ruti Levtov; Joya Banerjee; Myra Betron; Reena Sethi; Marie Rose Kayirangwa; Kristina Vlahovicova; Felix Sayinzoga; Rosemary Morgan (BMC, 2021)
Abstract Background Rwanda has made great progress in improving reproductive, maternal, and newborn health (RMNH) care; however, barriers to ensuring timely and full RMNH service utilization persist, including women's limited decision-making power and poor-quality care. This study sought to better understand whether and how gender and power dynamics between providers and clients affect their perceptions and experiences of quality care during antenatal care, labor and childbirth. Methods This mixed methods study included a self-administered survey with 151 RMNH providers with questions on attitudes about gender roles, RMNH care, provider-client relations, labor and childbirth, which took place between January to February 2018. Two separate factor analyses were conducted on provider responses to create a Gender Attitudes Scale and an RMNH Quality of Care Scale. Three focus group discussions (FGDs) conducted in February 2019 with RMNH providers, female and male clients, explored attitudes about gender norms, provision and quality of RMNH care, provider-client interactions and power dynamics, and men's involvement. Data were analyzed thematically. Results Inequitable gender norms and attitudes - among both RMNH care providers and clients - impact the quality of RMNH care. The qualitative results illustrate how gender norms and attitudes influence the provision of care and provider-client interactions, in addition to the impact of men's involvement on the quality of care. Complementing this finding, the survey found a relationship between health providers' gender attitudes and their attitudes towards quality RMNH care: gender equitable attitudes were associated with greater support for respectful, quality RMNH care. Conclusions Our findings suggest that gender attitudes and power dynamics between providers and their clients, and between female clients and their partners, can negatively impact the utilization and provision of quality RMNH care. There is a need for capacity building efforts to challenge health providers' inequitable gender attitudes and practices and equip them to be aware of gender and power dynamics between themselves and their clients. These efforts can be made alongside community interventions to transform harmful gender norms, including those that increase women's agency and autonomy over their bodies and their health care, promote uptake of health services, and improve couple power dynamics.